![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)(-35)÷5-(-25)×(-4)(2)(-3)2-(-32)+(-42)+(-4)2(3)2×(-3)2?5÷12×2
计算:(1)(-35)÷5-(-25)×(-4)(2)(-3)2-(-32)+(-42)+(-4)2(3)2×(-3)2?5÷12×2(4)7a2b+(-4a2b+5ab...
计算:(1)(-35)÷5-(-25)×(-4)(2)(-3)2-(-32)+(-42)+(-4)2(3)2×(-3)2?5÷12×2(4)7a2b+(-4a2b+5ab2)-(2a2b-3ab2)
展开
1个回答
展开全部
(1)原式=-7-100
=-107;
(2)原式=9-(-9)+(-16)+16
=9+9+(-16)+16
=18;
(3)原式=2×9-5×2×2
=18-20
=-2;
(4)原式=7a2b-4a2b+5ab2-2a2b+3ab2
=a2b+8ab2.
=-107;
(2)原式=9-(-9)+(-16)+16
=9+9+(-16)+16
=18;
(3)原式=2×9-5×2×2
=18-20
=-2;
(4)原式=7a2b-4a2b+5ab2-2a2b+3ab2
=a2b+8ab2.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询